Pengelolaan Pengadaan Barang Operasional Restoran Skyline Di Hotel Ibis Padang - Nur Anisa (JURNAL PENDIDIKAN DAN KELUARGA, 2018)
Abstract.This research is motivated by the poor management of the procurement of skyline restaurant operational goods due to the frequent situation of urgent goods but the user rarely directly engages in receiving goods, is not right in planning procurement of goods, organizational structure is not lived properly, and lack of communication in ordering goods. This research is a descriptive study with a qualitative approach. The sampling technique used was purposive sampling which consisted of purchasing staff and F&B Manager. Data collection techniques are carried out using interview, observation, and documentation methods. Data analysis techniques are used through three stages, namely: data reduction, data presentation, and conclusion.Based on the results of research conducted, it was found several things related to the management of the procurement of skyline restaurant operational goods, namely: purchase requests, supplier selection, purchase orders, receipt of goods, and recording of purchase transactions whose entire process must pay attention to several management functions including planning, organizing, directing and monitoring so that the management of the skyline restaurant operational goods procurement runs well and there is no loss for employees or hotels. Keywords: Management, Procurement of goods, Restaurant